Are medical students aware of surgical checklist and basics of patient safety in the OR? - Medical University of Lublin experience - Golebiowska, Maria; Golebiowska, Beata (Journal of Education, Health and Sport, 2018)
WHO Surgical Checklist is a tool created for the operating teams in order to provide a surgical safety track of procedures, unified in a worldwide scale. Patient safety is still the biggest challenge of healthcare, despite the introduction of newest technology and medicine overcoming plenty of surgical challenges in modern surgery. Among 8% of all adverse events are surgical adverse events, and nearly half of them could be easily preventable. That is why the aim of our study is to examine the awareness and knowledge level of medical students about surgical safety procedures. For this purpose, the survey on the basic understanding of surgical checklist and patient safety within surgical procedures was distributed during surgical workshops both basic and advanced skills in years 2015-2016 for 115 students. Respondents age, country of origin, year of study, previous attendance to surgical procedures information was also obtained. Our study proved, that the vast majority of medical students interested in surgical fields as their future profession are unaware of surgical safety procedures and its basic terminology (85% of respondents). The highest response of correct answers was noted within sign out procedures - post surgical check-up within the OR (74%). The Surgical Safety Checklist unifies the process of avoiding human error in surgery at all costs. However, despite 15 years of introduction to the surgical field, the medical education methods among undergraduate students are still insufficient. This should be changed in order to save more lives and provide better health care for all, with the most important principle in mind - first, do no harm.